Tata rias pengantin dan adat pernikahan gaya Yogyakarta klasik corak puteri / R. Sri Supadmi Murtiadji, R. Suwardanidjaja ; editor, Nana Lystiani. - SRI SUPADMI MURTIADJI, R.; Suwardanidjaja, R.; Nana Lystiani (Gramedia Pustaka Utama, 2012)
103 hlm. : ilus. ; 27 cm (3 eks.)